Characterization of Tamarindus indica L. Leaves Herbal Tea as a Functional Beverage - Khoirin, Maghfiroh; ., Mutmainah; Cahyaning Rini, Utami; Deny, Utomo; M. Aniar, Hari S; Hapsari Titi, Palupi (INTI International University, 2025)
Tamarindus indica leaves possess great potential as they are rich in antioxidants and suitable for consumption as a functional beverage. Processing T. indica leaves into herbal tea can enhance their usability and benefits. This study aimed to investigate the effect of drying time and temperature on the quality of T. indica leaves herbal tea and the antioxidant characteristics of its infusion. A Randomized Block Design (RBD) was employed with two factors: drying time (2 and 3 hours) and drying temperature (40°C, 50°C, 60°C), resulting in six treatment combinations, each replicated three times. The parameters analyzed in the tea powder included moisture content, ash content, and color intensity (L, a*, b*), while the infusion was analyzed for antioxidant activity, pH, and organoleptic properties (color, aroma, and taste). The results showed that both drying time and temperature significantly affected the moisture content, ash content, color intensity (L, a*, b*), antioxidant activity, pH, and sensory attributes. The best treatment was drying for 2 hours at 40°C, producing a tea with moisture content of 3.13%, ash content of 5.20%, color intensity L = 57.12, a* = 6.10, b* = 16.68, antioxidant activity of 8.24%, pH of 2.70, and organoleptic scores (neutral) for color (3.36), aroma (3.32), and taste (3.36).